Sayyed Hossein Nasr tentang Filsafat Perennial dan Human Spiritualitas - Jaipuri Harahap (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2017)
According to Hossein Nasr, what is occurred on the failure of Western civilization nowadays is because of their effort to isolate human being form its essence by eliminating human spirituality as a pillar of civilization itself. To dealt with, Nasr offered a solution through perennial philosophy that is a new knowledge approach integrated spiritual and rational dimension of philosophy which back to divine revelation, called traditional philosophy.Through perennial philosophy, then, Nasr tried lead human being to an awareness of that only God is an absolute thing, source of all things, including religious plurality and any religious sites. Therefore, Nasr ask to find each similarity and difference to encourage positive doctrine from it primordial, not to create enmity.